A Case of Acquired Factor V Deficiency in Patient with Bleeding - Davide Vetri; Giovanni Lumera; Salvatore Tarascio; Salvatore Scuto; Elisa Marino; Giuliana Barcellona; Salvatore Santo Signorelli (TH Open, 2020)
Low frequency of rare diseases origins from missed diagnosis addressing to poor prognosis. Acquired factor V inhibitor is a very low frequent bleeding condition (prevalence: 0.09/100,000,000–0.29/1,000,000 per year). Antibiotics, surgery, bacterial infections, malignancies, and autoimmune diseases are predisposing factors; however, no predisposing factor was found often. Authors reported a case of bleeding originating from an acquired factor V deficiency because they wish to draw attention to unfrequented or rare clinical situations rarely diagnosed in internal medicine unit.